2022
DOI: 10.7759/cureus.32722
|View full text |Cite
|
Sign up to set email alerts
|

Expediting the Management of Suspected Cauda Equina Syndrome (CES) in the Emergency Department Through Clinical Pathway Design at a District General Hospital: A Quality Improvement Project

Abstract: Background: Cauda equina syndrome (CES) is an uncommon condition that occurs due to compression of the terminal portion of the spinal cord. Early recognition and intervention in CES are crucial for an improved prognosis. Delayed diagnosis and action may lead to irreversible adverse effects, i.e., permanent disability, and in some circumstances can lead to litigation. Aim: The aim of this quality improvement project (QIP) was to identify areas for improvement and expedite the management of suspected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…We believe this was due to accurate and prompt assessment, which permitted earlier MRI requests as a direct result; faster diagnosis and management. This is similar to findings in Nasim et al's paper where it was shown that the earlier the MRI scans are requested upon initial patient assessment, the shorter the inpatient stay for these patients [15].…”
Section: Discussionsupporting
confidence: 89%
“…We believe this was due to accurate and prompt assessment, which permitted earlier MRI requests as a direct result; faster diagnosis and management. This is similar to findings in Nasim et al's paper where it was shown that the earlier the MRI scans are requested upon initial patient assessment, the shorter the inpatient stay for these patients [15].…”
Section: Discussionsupporting
confidence: 89%
“…The symptoms include lower extremity paralysis, sensory deficits in the “saddle” area, and dysfunction of bladder and bowel control. CES is typically caused by conditions that lead to acute compression of nerve roots, such as herniated discs, tumors, infections, and traumatic spinal injuries [ [1] , [2] , [3] , [4] , [5] ].…”
Section: Introductionmentioning
confidence: 99%